Bank accounts and savings - the impact of remittances and migration: a case study of Moldova - Fernando Rios Avila; Eva Schlarb (Kiel Institute for the World Economy (IfW), 2008)
In many developing countries, the formal financial sector is underdeveloped and majority of the population does not have access to it. This paper analyzes the empirical link between remittances and financial sector development on a microeconomic level. Using a unique household dataset for Moldova, we find that receiving monetary remittances has a positive and significant effect on the probability of having a bank account, thereby promoting financial sector development. Furthermore, we show that remittances tend to have an even higher positive effect on household savings, which is a sign for a hidden potential for financial sector development.
Keywords: 330; Rücküberweisung (Migranten); Sparen; Finanzsektor; Entwicklung; Moldawien